How a little becomes a lot : the art of small changes for a more meaningful life - Zimmer, Eric (Podcaster) (Harvest, an imprint of William Morrow, 2026)
"Drawing on sources from Zen Buddhism to modern psychology, Zimmer offers practical wisdom you can use today: a path to align your daily actions with your core values; tools that quiet self-criticism and build the kind of self-compassion that actually works; small, achievable practices that create momentum when you feel stuck; ways to find balance in a world that pushes extremes" -- Provided by publisher